2011
DOI: 10.1007/s12663-011-0248-3
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Congenital Granular Cell Epulis in the Maxillary Anterior Ridge: A Study of Cell Proliferation Using Immunohistological Staining

Abstract: Congenital granular cell epulis (CGCE) is a very rare benign tumor that preferentially develops in female infants. The histopathological characteristics of CGCE are very similar to a granular cell tumor, but the histological genesis is unknown. We report a case of a fourday-old female neonate who had a tumor mass in the region of the left maxillary anterior teeth. The rate of cell proliferation was determined by immunostaining with Ki-67 and PCNA, which showed labeling indexes of 16.7 and 15.1%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In the present case, a low number of cells were Ki-67 positive, suggesting minimal cell proliferation, which was unexpected as CGCE is considered a recently formed lesion. This result is in agreement with Kato et al [ 10 ], who demonstrated a labeling index of 16.7% for CGCE granular cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present case, a low number of cells were Ki-67 positive, suggesting minimal cell proliferation, which was unexpected as CGCE is considered a recently formed lesion. This result is in agreement with Kato et al [ 10 ], who demonstrated a labeling index of 16.7% for CGCE granular cells.…”
Section: Discussionsupporting
confidence: 93%
“…The principal histological differential diagnosis of CGCE is granular cell tumor (GCT). Both lesions are histologically similar; however, when considering the clinical, morphological, and immunohistochemical features together, it becomes possible to distinguish one from the other [ 3 , 10 , 11 ]. GCT is composed of large polygonal cells with an abundant granular eosinophilic cytoplasm arranged in layers, cords, or nests, with pseudoepitheliomatous hyperplasia of the epithelium and small peripheral nerves are often observed [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CGCE tends to distinctively stain negative for S-100, laminin, CD34, CD68, NGFR/ p75, inhibin-alpha, chromogranin, desmin, keratins, smooth muscle actin, CD31, and GLUT-1 and conversely stains positive for vimentin and neuron-specific enolase [2,3,14]. Proliferation index of CGCE determined by Ki-67 and PCNA immunostaining is reported to be 11.1-16.7% and 15.1-33.3%, respectively [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although many immunohistochemical outcomes have been demonstrated (10)(11)(12)(13)(14), the exact histogenesis of CGCT is still unclear. The possible cellular origins include epithelial, undifferentiated mesenchymal cells, pericytes, fibroblasts, smooth muscle cells, and nerve-related cells (13).…”
Section: Hypothesis Of Histogenesis and Aetiologymentioning
confidence: 99%